Fungal zinc metabolism and its connections to virulence - Staats, Charley C.; Kmetzsch, Livia; Schrank, Augusto; Vainstein, Marilene H. (Frontiers in Cellular and Infection Microbiology, 2013)
Zinc is a ubiquitous metal in all life forms, as it is a structural component of the almost 10% of eukaryotic proteins, which are called zinc-binding proteins. In zinc-limiting conditions such as those found during infection, pathogenic fungi activate the expression of several systems to enhance the uptake of zinc. These systems include ZIP transporters (solute carrier 39 family) and secreted zincophores, which are proteins that are able to chelate zinc. The expression of some fungal zinc uptake systems are regulated by a master regulator (Zap1), first characterized in the yeast Saccharomyces cerevisiae. In this review, we highlight features of zinc uptake and metabolism in human fungal pathogens and aspects of the relationship between proper zinc metabolism and the expression of virulence factors and adaptation to the host habitat.